PROBLEMATIKA IMPLEMENTATIF CORPORATE SOCIAL RESPONSIBILITY PADA BANK SYARIAH DI INDONESI - Zumaroh Zumaroh; Desi Wahyuni (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2019)
This paper aims to examine the implementation of social responsibility (Corporate Social Responsibility) in Islamic banks. This study also includes a review of the usefulness of social responsibility (CSR) Sharia banking based on applicable regulations. Practically, this study is expected to be able to contribute to Islamic Financial Institutions (LKS), especially Islamic Banks in making decisions and determining Social Responsibility (CSR) programs for the interests of stakeholders. This type of research is qualitative, with analytical descriptive method and philosophical normative approach. The results showed that in the implementation of CSR in Islamic banks there were problems in management because CSR funds were managed together with ZIS funds. With regulations that can be combined, Islamic banks are able to more effectively carry out their social functions as a form of accountability to all parties involved with the company, both employees and stakeholders. Optimal application of CSR can improve the sustainability of Islamic banks because of the increasing image of the bank in the eyes of the general public